2021
DOI: 10.3390/cryst11121583
|View full text |Cite
|
Sign up to set email alerts
|

Ultrathin and Optically Transparent Microwave Absorber Based on Flexible Silver Nanowire Film

Abstract: The design of an optically transparent and flexible metamaterial absorber was presented and fabricated. For this purpose, we use two different patterned silver nanowire films separated by the space layer, forming a transparent sandwiched structure with an ultrathin thickness. By analyzing the equivalent circuit model and distribution of electric field and current, the absorption physical mechanism has been theoretically investigated. The results show that the structure can achieve above 0.8 absorptions from 6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…Constructing devices with transparent substances such as polyethylene terephthalate (PET) and polymethyl methacrylate (PMMA) is one such strategy [17][18][19]. Moreover, transparent conductive materials such as indium tin oxide (ITO) and silver nanowires are viable options [20,21]. Structurally, transparency is achieved by reducing the area ratio of non-transparent materials in the MMA composition.…”
Section: Introductionmentioning
confidence: 99%
“…Constructing devices with transparent substances such as polyethylene terephthalate (PET) and polymethyl methacrylate (PMMA) is one such strategy [17][18][19]. Moreover, transparent conductive materials such as indium tin oxide (ITO) and silver nanowires are viable options [20,21]. Structurally, transparency is achieved by reducing the area ratio of non-transparent materials in the MMA composition.…”
Section: Introductionmentioning
confidence: 99%
“…Microwave-absorbing materials with optical transparency and structural flexibility are extremely beneficial to stealth technology in some special components of aircraft, such as solar energy panels, cockpit windows, and sophisticated optical machines. For example, as shown in Figure a, the panels on satellites or airplanes coated with microwave-absorbing metasurfaces can utilize solar energy effectively without worry of detection by outside microwave radar systems. Moreover, the flexible structure allows absorbers conformally applied to curved surfaces that further improved the aerodynamics of aircraft. , In recent years, a variety of metasurface absorbers with visibility and flexibility are experimentally proposed based on transparent conducting materials with uniformly arranged nanoparticles, such as indium tin oxides (ITO), oxide–metal–oxide structure, and metallic nanowires. Dong et al experimentally demonstrated a 0.065-wavelength-thick electromagnetic camouflage metasurface based on metallic nanowires, which can achieve 88% of the optical transmittance and broadband microwave absorption from 7.2 to 18.5 GHz. Xu et al proposed an optically transparent microwave cloak that integrates longwave cloaking and shortwave invisibility simultaneously.…”
Section: Introductionmentioning
confidence: 99%